2016
DOI: 10.1088/1748-6041/11/6/065010
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the potential risk of amyloidosis from exposure to silk fibroin

Abstract: Amyloid A (AA) amyloidosis can be induced by the administration of amyloid fibrils to animals under inflammatory conditions. Silk fibroin (SF) is a main component protein of bombic silk and has amyloid-like features. The amyloidogenesis of SF solution in mice has been previously reported. Recently, the biochemical properties of silk have attracted increasing attention, and research and development have been undertaken regarding applications other than as a clothing material. However, the risk of AA amyloidosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Currently, despite centuries of use, there appears to be little evidence that human amyloidosis has been caused by silk, but conversely there has also been insufficient specific long-term investigation. A low potential for amyloidosis 72 needs to be risk-assessed with long-term studies for specific sites involving simultaneous inflammation. 69 First, to do no harm, remains a basic tenet of medical treatment and potential harm needs to be fully assessed before fibroin is used as a biomaterial in the eye.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, despite centuries of use, there appears to be little evidence that human amyloidosis has been caused by silk, but conversely there has also been insufficient specific long-term investigation. A low potential for amyloidosis 72 needs to be risk-assessed with long-term studies for specific sites involving simultaneous inflammation. 69 First, to do no harm, remains a basic tenet of medical treatment and potential harm needs to be fully assessed before fibroin is used as a biomaterial in the eye.…”
Section: Discussionmentioning
confidence: 99%
“…Fibroin has also been shown to be a relatively poor seed in Aβ40 and Aβ42 aggregation. 49 A direct study of the risk of fibroin for amyloidosis by Tsukawak et al, 72 concluded that silk occasionally promotes amyloidogenesis, but has a low potential for amyloidosis. Amyloid deposits were rarely observed in mice injected with silk fibroin in solution, but with certain methods of production, heavy amyloid deposit resulted from fibroin fabric placed in the abdomen; the production method is an important determinant of its biocompatibility.…”
Section: Association Of Fibroin β-Sheet With Amyloid and Amyloidosismentioning
confidence: 99%
“…This non-woven scaffold is considered to be effective for the migration, attachment, and infiltration of cells, which are suitable advantages for regenerative sheets. 10,22,24…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical staining was performed with the Envision+ kit (Dako, Carpinteria, CA, USA), using the following freshly prepared primary antibodies: monoclonal rabbit anti-CD34 antibody (ab81289, 1:100, Abcam, Cambridge, UK), polyclonal rabbit anti-alpha smooth muscle actin (alpha-SMA) antibody (ab5694, Abcam, Cambridge, UK), polyclonal rabbit anti-Iba1 antibody (013-27691, FUJIFILM Wako Pure Chemical Corporation, Japan), and rabbit anti-SF serum (1:80,000). 22…”
Section: Methodsmentioning
confidence: 99%
“…The assessment of the adverse effects upon exposure (by ingestion or inhalation) to materials containing pathological amyloid brils is still under study. [36][37][38] At present, global safety guidelines and/or protocols for handling this type of material are not yet fully dened. However, there start to be converging opinions that the use of food-based amyloids, as in the present case, is safe for human consumption.…”
Section: Safety and Protection Measuresmentioning
confidence: 99%